Evaluation of YouTube Audio Teaching Materials for Blind Students at SLB-A Beringin Bhakti - Rivanda Yuliani; Monica Astriyanti Sukardi (JEES: Journal of Education and Educational Sciences, 2024)
This study was conducted at Beringin Bhakti Special School (SLB) with the aim of evaluating the teaching media used by teachers during lessons. The research is titled "Evaluation of YouTube Audio Learning Materials for Blind Junior High School Students at SLB-A Beringin Bhakti." The main questions posed in this study include what teaching materials are used and the students' responses to the use of these materials. This research employs a qualitative approach with a focus on case studies to explore the evaluation of audio learning materials in the education of blind junior high school students at SLB-A Beringin Bhakti. The case study approach allows the researcher to investigate in-depth the interactions between students, teachers, and audio learning materials in a real context. The sample of this study consists of one blind student and one accompanying teacher who actively use audio learning materials in their lessons. Data collection techniques include observation, interviews, and documentation. The evaluation results indicate that YouTube audio learning materials have great potential in enhancing the learning experience of blind students at SLB-A Beringin Bhakti. However, efforts are needed to improve technical infrastructure and support to maximize the benefits of using these learning materials.